Terokal consumption in stree children - Castamán Díaz, Desirée (2005)
The article intends to focus street children´s problems. It show then from a social-economic and historial point of view. Terokal consumption in street is their way to escape from cold, hunger and maltreatment, translating it into an espace from reality they live in their homes and in street. At the end, "Instituto Generación" presents an experience with street children.